2016
DOI: 10.1248/bpb.b15-00699
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotection of Osthole against Cerebral Ischemia/Reperfusion Injury through an Anti-apoptotic Pathway in Rats

Abstract: Cerebral ischemia/reperfusion (I/R) injury is a major cause of acute brain injury. The pathogenetic mechanisms underlying I/R injury involve apoptosis, inflammation and oxidative stress. Osthole-a plant coumarin compound-has been reported to protect against focal cerebral I/R-induced injury in rats. However, the mechanism remains unknown. Here we hypothesize that osthole acts through inhibition of apoptosis during focal cerebral I/R injury in rats. We induced cerebral I/R injury by middle cerebral artery occlu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(37 citation statements)
references
References 28 publications
1
35
0
1
Order By: Relevance
“…Ischemic stroke is a serious threat to human health and is the most frequent cause of permanent disability in adults worldwide (Lozano et al, 2012). The pathophysiological processes in ischemic stroke are diverse, and include inflammation, apoptosis, oxidative stress, intracellular calcium overload, and destruction of the blood brain barrier (BBB) (Tobin et al, 2014;Li et al, 2016;Li et al, 2018a). TCM herbs and their components have been widely used as therapeutic agents in China since ancient times (Sun et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Ischemic stroke is a serious threat to human health and is the most frequent cause of permanent disability in adults worldwide (Lozano et al, 2012). The pathophysiological processes in ischemic stroke are diverse, and include inflammation, apoptosis, oxidative stress, intracellular calcium overload, and destruction of the blood brain barrier (BBB) (Tobin et al, 2014;Li et al, 2016;Li et al, 2018a). TCM herbs and their components have been widely used as therapeutic agents in China since ancient times (Sun et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis is an autonomic ordered programmed cell death in order to maintain homeostasis, which is controlled by polygenes. 20,21) Several lines of evidence have shown that apoptosis plays an important role in the pathogenesis of various human diseases, including cerebral I/R injury. During cerebral ischemia, both cyclooxygenase-2 and inducible nitric oxide synthase are highly expressed, and induce activated microglial cells to generate ROS.…”
Section: Discussionmentioning
confidence: 99%
“…Another natural prenylated coumarin is osthole (7-methoxy-8-(3-methylbut-2-en-1-yl)-2H-chromen-2-one) founded in many plants and showed antifungal activity, [18] antioxidant and neuroprotective properties in the brain from cerebral ischemia/reperfusion injury. [19,20] Moreover, it has been revealed that a number of derivatives of 7-hydroxycoumarins containing bicyclic monoterpene substituent at the hydroxy group are capable of enhancing the cytotoxicity of camptothecin. [21] This compounds also demonstrate inhibition activity against influenza virus A/California/07/09 (H1 N1)pdm09.…”
Section: Introductionmentioning
confidence: 99%